Electronic Atlas “Ukraine. Cultural And Landscape Heritage”: Conceptual Foundations and Experience of Creation - Polyvach, K. A. (Ukrainian Geographical Journal, 2025)
This study aims to present the main conceptual and methodological approaches to the consideration of the cultural and landscape heritage of Ukraine as a subject of scientific research and the results of its cartographic visualization in the form of a thematic electronic atlas. The electronic atlas, “Ukraine. The Cultural and Landscape Heritage,” was established as a key strategy to accelerate the practical implementation and popularization of the cultural and landscape approach to protecting, preserving, and managing Ukraine’s cultural and natural heritage. The atlas was created based on the elaborated concept of understanding and developing cultural and landscape heritage, allowing spatial information to be structured and visualized. As a result, the first national electronic cartographic product on this topic was created, which provided a spatial representation of the peculiarities of Ukraine’s cultural and landscape heritage. The distribution and use of the atlas will contribute to further developing thematic mapping and atlas geographic information systems for the protection and preservation of cultural and natural heritage.